(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تناولت هذه الدراسة توزع الفحوم الهيدروجينية متعددة النوى العطرية (PAHs) في الرسوبيات الشاطئية لمدينة اللاذقية حيث تم تحديد تراكيزها في 110 عينة من العينات الرسوبية الشاطئية السطحية، تم اعتيانها من سبعة مواقع منتشرة على طول شاطئ مدينة اللاذقية وذلك خلال الفترة الممتدة ما بين 7 / 5 / 2000 و21 / 6 / 2001، مستخدمين تقانة الكروماتوغرافيا الغازية (GC) المجهزة بنظام حقن بالتجزئة ودون التجزئة (Split/splitless)، وعمود شعري، وكاشف تشرد اللهب FID ومعتمدين في ذلك على محاليل عيارية خارجية وداخلية. تراوحت تراكيز الفحوم الهيدروجينية متعددة النوى العطرية في العينات الرسوبية ما بين (dry wt.) ng/g(11.6-562.67)، وُسجلت أعلى قيمة في الموقع St(d) نتيجة للنشاط البشري الكبير في يمين المدخل الشمالي للمرفأ التجاري، وأخفض قيمة في الموقع St(g) في منتجع الشاطئ الأزرق، لعدم وجود مصادر تلوث قريبة من تلك المنطقة. تشير هذه الدراسة إلى أن تراكيز المركبات متعددة النوى العطرية هي ضمن حدود التأثيرات المنخفضة Effect Range Low ERL (<4ppm). This study deals with the distribution of Polycyclic Aromatic Hydrocarbons (PAHs) in tidal sediments of Lattakia coast. The concentrations of polycyclic Aromatic Hydrocarbons were determined in (110) surface samples of sediments taken from seven tidal sites along Lattakia coast, during the period 7 / 5 / 2000 – 21 / 6 / 2001, using the technique of Gas Chromatography (GC) was equipped with a Split/Splitless injection system, Capillary column, Flame Ionization Detector (FID) and depending on External &Internal Standard solutions. The concentration of total polycyclic Aromatic Hydrocarbons (ΣPAHs) in sediment samples ranged between (562.67-11.6) ng/g dry wt, The highest concentration was reported in St(d); resulting of the existing human activities to the right of northern entrance gate of commercial port, and the lowest value was reported in St(g) (i.e the blue Coast resort), due to lack of pollution sources near this region. This study indicates that the concentrations of Polycyclic Aromatic Hydrocarbons is fall within the Effect Range Low (ERL) (4ppm).